`Implikasi Hukum Terhadap Peralihan Hak Atas Tanah Didasarkan pada Perjanjian Jual Beli di Bawah Tangan: Studi Putusan Pengadilan Negeri Bekasi Nomor: 129/Pdt.G/2016/PN Bks - Muhamad Irham Husni Mubarok (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Purchase Land is a source of life necessities for humans, because land functions as a means to find life. As the number of people increases to fulfill their daily needs, land is very necessary for use as land for housing to be built as a place to live. In the case of Bekasi District Court Decision Number: 129/Pdt.G/2016/PN Bks. It started when the defendant, Yulius Caesarius Panirman, sold the rights to a plot of land in the form of a building use certificate to the plaintiff, Handoko. The sale and purchase agreement for land rights was only carried out privately, so that when the sale and purchase occurred from the Defendant to the Plaintiff, an oral agreement had occurred, namely the Defendant promised to be present to carry out the transaction and signed the sale and purchase deed before a Notary and PPAT. In this research, we will discuss how the legal implications for the transfer of land rights are based on the land sale and purchase agreement that was made privately in Decision Number 129/Pdt.G/2016/PN.Bks and what is the basis of the Judge's Legal Considerations in the Case Settlement Process in the Decision Number 129/Pdt.G/2016/PN.Bks is in accordance with the Legal Certainty Theory. By using a normative juridical approach with literature study to analyze relevant laws and regulations. to guarantee legal certainty of the deed made. It is necessary to make a PPAT Deed because the PPAT Deed is an authentic deed and as an authentic deed there are strict requirements in terms of preparation procedures, forms and formalities that must be carried out so that the deed has the right to be called an authentic deed.